Penerapan sakralitas pada arsitektur Vihara - Museum Buddha - Singgih Salim; Rahadhian Prajudi Herwindo; Yuswadi Saliya (ARTEKS : Jurnal Teknik Arsitektur, 2022)
Buddhism is one of the oldest religions in the world, and the development has led to a great change in the typology of Buddhist architecture, and caused a complex scope of the concept. This complexity is due to the absence of architectural literature that regulates the addition of supporting functions, such as profane and sacred value, in improving Buddhists' education. However, the addition of a profane function reduces sacred value and act of worship, opposes architectural design, and defiles ritual activities. Furthermore, one of the functions that provide education as well as a personal approach to Buddhism is the museum. This research aims to examine the contextual relationship between main and supporting functions, namely the sacred (worship building) and the profane (museum), respectively. And also, to display the sacred value through architectural characteristics. The analytical method used the theory of sacredness and contextuality. This was further elaborated in various architectural scopes to produce a relationship between temples and museums, that apply sacred values according to Buddhist philosophy. The research leads to differences in principles application, such as orientation, hierarchy, boundary scope, geometric shapes, symmetry, repetition, material appearance, shape synergy, zoning, processions, atmospheric ambiguity, symbolic objects, boundary guards, and gathering areas.